2016
DOI: 10.1097/fbp.0000000000000250
|View full text |Cite
|
Sign up to set email alerts
|

Real-time assessment of alcohol drinking and drug use in opioid-dependent polydrug users

Abstract: We investigated relationships between drinking, other drug use, and drug craving, using ecological momentary assessment (EMA), in a sample of polydrug users who were not heavy drinkers. In a prospective longitudinal cohort study, 114 heroin and cocaine users in methadone-maintenance treatment carried handheld electronic diaries during waking hours and were screened for drug and alcohol use for up to 25 weeks. Individuals who met DSM criteria for alcohol abuse or dependence were excluded. Participants responded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Some of the more commonly studied polydrug combinations include administration of cocaine with other drugs (Francesco et al, 2003;Leri et al, 2003b; Substance Abuse and Mental Health Services Administration, 2016). However, in contrast to human reports (Heil et al, 2001;Williamson et al, 2006;Staiger et al, 2013;Preston et al, 2016;Lorvick et al, 2018;Kariisa et al, 2019), an increase in addiction-like severity has not been observed in preclinical studies, suggesting a need for models with greater translational relevance that can capture the enhanced severity seen in human polysubstance users. Specifically, animal studies of sequential cocaine and alcohol or cocaine and heroin use have not found differences in drug intake or reinstatement of drug-seeking as a function of single versus polydrug use (Pattison et al, 2014;Fredriksson et al, 2017;Crummy et al, 2020;Stennett et al, 2020).…”
Section: Psychostimulantsmentioning
confidence: 75%
See 1 more Smart Citation
“…Some of the more commonly studied polydrug combinations include administration of cocaine with other drugs (Francesco et al, 2003;Leri et al, 2003b; Substance Abuse and Mental Health Services Administration, 2016). However, in contrast to human reports (Heil et al, 2001;Williamson et al, 2006;Staiger et al, 2013;Preston et al, 2016;Lorvick et al, 2018;Kariisa et al, 2019), an increase in addiction-like severity has not been observed in preclinical studies, suggesting a need for models with greater translational relevance that can capture the enhanced severity seen in human polysubstance users. Specifically, animal studies of sequential cocaine and alcohol or cocaine and heroin use have not found differences in drug intake or reinstatement of drug-seeking as a function of single versus polydrug use (Pattison et al, 2014;Fredriksson et al, 2017;Crummy et al, 2020;Stennett et al, 2020).…”
Section: Psychostimulantsmentioning
confidence: 75%
“…Polydrug use increases the risk of developing an alcohol use disorder (Grant et al, 2015(Grant et al, , 2016, particularly in young adults, men, and American Indians/Alaskan Natives (Falk et al, 2006). Polydrug use that includes alcohol is associated with additional comorbidities, including higher prevalence of mood disorders, anxiety disorders, more intense drinking, and more intense drug consumption and drug-craving (Preston et al, 2016;Saha et al, 2018). The negative consequences of alcohol polydrug use are also highlighted by data indicating that 21% of ED visits for patients 12-24 years old involved both alcohol and drugs.…”
Section: Alcoholmentioning
confidence: 99%
“…In Taiwan, the frequency of cocaine use is low; however, the frequency of amphetamine use, a cocaine-like stimulant, is high in clients with HUD 57 . It might be due to most individuals with HUD abusing other substance such as amphetamine 58 , 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Detailed characterization of drinking patterns in the field has been difficult in the past but may be facilitated by recent technological advances. For example, ecological momentary assessment has been used to provide temporal and geospatial profiles of drug and alcohol use . Such assessments should eventually be coupled with real‐time blood alcohol level measurement using wearable biosensors .…”
Section: Discussionmentioning
confidence: 99%